The Role of Artificial Intelligence in Surgical Procedures: A Comprehensive Review - Fatin Riyadh jawad alhoudar et al. (International Journal of Scientific Research and Innovative Studies, 2024)
The application of artificial intelligence (AI) in surgery is revolutionizing the field of medicine, offering new possibilities for precision, efficiency, and patient outcomes. AI technologies, such as machine learning (ML), computer vision, and natural language processing, are now integral to various aspects of surgical practice, from preoperative planning and intraoperative navigation to postoperative care and training. This review explores the current and emerging roles of AI in surgical procedures, focusing on robotic-assisted surgery, image-guided interventions, predictive analytics, and personalized treatment approaches. It also addresses the challenges and ethical considerations associated with implementing AI in surgical practice. Key words: Artificial intelligence , health care , surgery Received Date: November 05, 2024 Accepted Date: November 26, 2024 Published Date: December 01, 2024 Available Online at https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/257 https://doi.org/10.5281/zenodo.14254293